2002
DOI: 10.1063/1.1501282
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of wave characteristics on a thin layer of de/anti-icing fluid

Abstract: Several series of experiments were conducted in order to investigate wave formation and wave characteristics on a thin layer of de/anti-icing fluid using a nonintrusive technique. The configuration consists of a thin layer of de/anti-icing fluid deposited on the lower wall of the wind tunnel section, sheared by a turbulent airflow. Beyond a critical value of the wind speed, two-dimensional surface waves could be observed. The characteristics of these waves like the wavelength and the wave speed could be measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…(23), the first three terms constitute the particular solution. The term of zero degree in y is taken to be zero, as demanded by condition (12). Boundary conditions (10), (11), and (14) assume the forms…”
Section: A Instability In the Long Wave Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…(23), the first three terms constitute the particular solution. The term of zero degree in y is taken to be zero, as demanded by condition (12). Boundary conditions (10), (11), and (14) assume the forms…”
Section: A Instability In the Long Wave Limitmentioning
confidence: 99%
“…Electronic mail: ariaz@umd.edu values of the Reynolds number. For large values of the Reynolds number, Özgen et al 12 found that shear modes dominate the instability behavior in the case of gas boundary layer over a newtonian liquid.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] When ice accumulates on the wings of aircraft, turbine engine structures, or insulators and transmission lines on power systems, it will impose serious problems and cause some disastrous damage in the aircraft and power industry. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] In the winter of 2008-2009, frozen rain lasted for more than three weeks in Hunan and Jiangxi provinces, causing downfall of 37% of Ice accumulation poses a series of severe issues in daily life. Inspired by the nature, superwettability surfaces have attracted great interests from fundamental research to anti-icing and ice-phobic applications.…”
Section: Introductionmentioning
confidence: 99%
“…In the LAbs technique the film thickness is retrieved by measuring the intensity of the light transmitted through the liquid film. Developed as a point-wise technique, using photodiods or photomultipliers as light receivers [14,15], the LAbs has later become a full field technique using digital video cameras and basic image processing operations [17][18][19]. While this method can provide high spatial and temporal resolution, its main limitation is in the assumption that the light transmittance is solely linked to light absorption, disregarding spurious effects such as light refraction, reflection or scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Time resolved, 2D and 3D film thickness measurements were performed using two measurement techniques. The first technique is the light absorption (LAbs), implemented in the 3D version used in [17][18][19]; the second technique is an adaptation of a visualization method based on planar laser-induced fluorescence (PLIF) and image processing, referred to as level detection and recording (LeDaR, [23][24][25]). In the LAbs technique the film thickness is retrieved by measuring the intensity of the light transmitted through the liquid film.…”
Section: Introductionmentioning
confidence: 99%